PERFORMANCE OF GINGER VAR. HUMNABAD AS INFLUENCED BY PLANTING DATES UNDER NORTHERN DRY ZONE OF KARNATAKA - A. SHADAP; N. K. HEGDE; A. PARIARI (The Bioscan, 2013)
A field experiment was conducted at the Department of Spices and Plantation Crops, K.R.C. College of Horticulture, Arabhavi, Belgaum District (Karnataka) to find out the optimum planting date for better growth, yield and quality in ginger var. Humnabad. Planting in the month of May took significantly lower number of days for germination (20.50). Maximum plant height was recorded in May planting (48.30cm) which was on par with June planting (47.93cm) compared to the minimum in March planting (27.11cm). The number of tillers per clump were higher in June planting (14.25) closely followed by May planting (14.05). May Planting also recorded higher fresh rhizome yield per hectare (17.09t) closely followed by June planting (16.49 t) while the lowest fresh rhizome yield was recorded by August planting (4.98t). Lower per cent disease intensity (Helminthosporium leaf spot) was recorded by May planting (22.87%) which was on par with June planting (28.26%) compared to the maximum in March planting (68.96%). Essential oil and oleoresin content was higher in March planting (1.62 and 4.55 % respectively) followed by April planting (1.51 and 4.35 % respectively) and the lowest was recorded by August planting (0.98 and 3.50 % respectively).